Effects of aqueous extract from Baiyedancong-Oolong tea on cytochrome P450 enzymes activities, P-gp and OATs transport abilities and transcription levels in mice - Zhang, Miaogao; Qiu, Zhenguo (Frontiers in Nutrition, 2023)
In this study, Baiyedancong Oolong tea (BOT) was processed by freeze- and hot air-drying techniques separately to obtain the aqueous extracts of freeze-and hot-dried BOT (FBOT and HBOT, respectively). High and low doses of FBOT (1463.7 and 292.74 mg/kg/d, respectively) and HBOT (1454.46 mg/kg/d, 290.89, respectively) were administered to mice for 7 days. The results showed that aqueous extracts from BOT simultaneously improved liver CYP3A, CYP2E1, and CYP2C37 activities and weakened the transport ability of P-gp and OATs in a dose-dependent manner, thus affecting multiple links of oral drug metabolism in liver, intestinal absorption and metabolism, and renal excretion. Moreover, aqueous extracts from BOT significantly increased the mRNA expressions of liver CYP3A11 and CYP2C37 as well as intestinal CYP3A11. Decreased transcription levels of MDR1 encoding P-gp in small intestine and renal OAT1 and OAT3, which was in the same direction as the regulation of the above enzyme activities and transport capacities. Besides, the transcription level of liver CYP2E1 was weakened, which was inconsistent with its corresponding enzyme activity, suggesting that the increased CYP2E1 activity may be caused by other mechanisms. Collectively, daily consumption or high dose administration of BOT and its related products may affect drug absorption, metabolisms, and excretion.